IMF Survey, Volume 36 Issue 04. (IMF Survey; IMF Survey ;, 2007)
Policy Support Instrument; PSI; Tanzania; quota reform; David Burton; basic votes; Andrew Tweedie; Abbas Mirakhor; Iqbal Zaidi; Rodrigo de Rato on Latin America; Brazil; sovereign debt; debt rigidity; financial sector regulation; health care; VAT fraud; pensions; Nicholas Stern; climate change.